2011
DOI: 10.1007/s11434-011-4627-4
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of the Compass satellite navigation system to global PNT users

Abstract: As one of the four global satellite navigation systems, Compass not only enhances satellite visibility and availability for positioning, navigation and timing (PNT) for users in China and the surrounding areas, but also improves PNT precision for global users. The improvements in satellite visibility and the dilution of precision are analyzed under GNSS compatibility and interoperation conditions. The contribution of the Compass satellite navigation system to global users, especially the benefits that users ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
121
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 262 publications
(121 citation statements)
references
References 3 publications
0
121
0
Order By: Relevance
“…A similar study was conducted by Yang et al [19], based on simulation, which has shown the enhancement in the satellite visibility, the availability and the DOP values thanks to the contribution of BeiDou to different combinations. It was found that GDOP and PDOP can be improved by 50% when BeiDou was combined with GPS.…”
Section: Introductionmentioning
confidence: 54%
“…A similar study was conducted by Yang et al [19], based on simulation, which has shown the enhancement in the satellite visibility, the availability and the DOP values thanks to the contribution of BeiDou to different combinations. It was found that GDOP and PDOP can be improved by 50% when BeiDou was combined with GPS.…”
Section: Introductionmentioning
confidence: 54%
“…The Geometric Dilution of Precision (GDOP) is an important parameter utilised in the propagation of random error (noise) in measurements of the noise levels of the unknown (solved for) parameters (Yang et al, 2011), and it is a quality measure to specify the additional multiplicative affect of measurement error on the positioning accuracy and the timing accuracy. Actually, the GDOP can be divided into the PDOP (Position Dilution Of Precision) and (Time Dilution Of Precision).…”
Section: Introduction the Future Of Global Navigation Satellite Systmentioning
confidence: 99%
“…Following the emergence and rapid development of other GNSS, i.e. GLObal NAvigation Satellite System (GLONASS), Galileo and the BeiDou Navigation Satellite System (BDS), GNSS are now stepping into a new era (Yang et al, 2011). With at least 70 to 80 visible GNSS satellites in the sky today, signals from at least 10 to 30 satellites could be received anywhere (excluding the North and South Poles) in the world.…”
Section: Introductionmentioning
confidence: 99%